2020
DOI: 10.1080/23748834.2020.1791441
|View full text |Cite
|
Sign up to set email alerts
|

Urban forms and green infrastructure – the implications for public health during the COVID-19 pandemic

Abstract: Recent health issues have raised awareness among the general public and stimulated debate over the future forms of urban living. Those factors which enhance healthier environments are receiving broader recognition in maintaining the health of citizens in a time of pandemic. The current article explores the framework of ecosystem services to examine the temporary interventions introduced in response to the current challenges. These short-term adjustments may indicate possible pathways for the future. Analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 4 publications
0
62
1
5
Order By: Relevance
“…Much previous research has reported the positive effects of urban green space on human health and well-being. Nevertheless, discussions regarding the role of UGS under extremely stressful circumstances (such as during a pandemic) are limited [53][54][55][56]. Therefore, this paper has identified self-reported patterns of urban green and blue space visitation before, during, and after COVID-19 restrictions and the perceived associated health and well-being benefits for a sample of city residents and also allow residents to meet their social interaction needs during the pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Much previous research has reported the positive effects of urban green space on human health and well-being. Nevertheless, discussions regarding the role of UGS under extremely stressful circumstances (such as during a pandemic) are limited [53][54][55][56]. Therefore, this paper has identified self-reported patterns of urban green and blue space visitation before, during, and after COVID-19 restrictions and the perceived associated health and well-being benefits for a sample of city residents and also allow residents to meet their social interaction needs during the pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Covid-19 has highlighted particular health challenges of water scarcity and heat. Examples include the difficulty of handwashing when water access is limited2324; the difficulty of socially isolating indoors when the temperature is extremely hot; and the paucity of green space and parks—important assets for restoration during the pandemic2526—in hot, dry places.…”
Section: Broader Context Mattersmentioning
confidence: 99%
“…The value and urgent need of urban nature during a time of pandemic, its importance for citizens are in the centre of researches worldwide (Hanzl, 2020;Venter, Barton, Gundersen, Figari & Nowell, 2020;Samuelsson, Barthel, Colding, Macassa & Giusti, 2020;Xie, Luo, Furuya & Sun, 2020;Kleinschroth & Kowarik, 2020;Lopez, Kennedy, & McPhearson, 2020). It is noted that urban green and large outdoor open spaces can provide residents with a place for safe outdoor activities and social interactions in a green environment during a pandemic and present resilient green infrastructure which value and significance are critical (Lopez, Kennedy, & McPhearson, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a common view on the future situation we can mention that the pandemic should influence on future planning (Rice, Mateer, Reigner, Newman, Lawhon & Taff, 2020;Lai, Leone, & Zoppi, 2020;Megahed & Ghoneim, 2020) and in the long run the COVID-19 crisis should induce for more sustainable city planning (Samuelsson, Barthel, Colding, Macassa & Giusti, 2020;Kleinschroth & Kowarik, 2020) in general and should generate spatial transformations in city planning and city settings (Hanzl, 2020) related to increasing and improving green infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%